Use of absorbable hemostat bolster for prevention of donor renal artery kinking in kidney transplant - Hawlina, Simon; Orožen, Blaž; Arnol, Miha; Kšela, Juš (Frontiers in Surgery, 2022)
Transplant renal artery stenosis due to mechanical kinking is a rare but significant complication in kidney transplantation that can lead to graft dysfunction due to graft hypoperfusion, delayed graft function, or even global kidney infarction. When detected during surgery, re-anastomosis is usually performed after re-clamping, which inevitably prolongs the warm ischemia time, and increases the possibility of primary graft non-function. In this report, we describe a novel, noninvasive surgical technique whereby the donor renal artery is padded with absorbable hemostatic material (i.e., Surgicel) bolster, placed below the middle third of the renal artery in recipients who were found to have mechanical kinking during the implantation procedure. The bolster technique was used in 12 kidney transplant recipients who were found to have kinking of the donor artery during the primary surgery. After pillowing the renal artery with absorbable hemostatic bolster, no residual kinking was observed intra-operatively, and good allograft perfusion was confirmed with no Doppler ultrasound evidence of renal artery stenosis confirmed at 1 week, 1 month, and 1 year after transplantation.